Knowledge and Attitude About COVID-19 Affected The Mental Health of Nurses - Rakhmawati, Wa Ode; Narmawan; Syahwal, Muh. (Asian Journal of Health and Applied Sciences, 2023)
Nurses are at the fore frontof taking care, prevention, and providing support and education almost at the same time without considering their psychological state in treating patients with Covid-19 for 24 hours. Most health workers have experienced and will experience some physical and psychological difficulties that are beyond their capacity. The importance of the knowledge and attitudes of nurses to provide professional nursing services during a pandemic has an impact on the ability of nurses to control the symptoms of mental health disorders. This study aimed to determine the relationship between knowledge and attitudes about Covid-19 and mental health of nurses. This research had a correlational design with a cross-sectional study approach. The study population was 109 nurses and 53 of them were taken by proportional random sampling technique. The correlation test was made using a Spearman rank test. This study suggested a moderate relationship between knowledge about Covid-19 and mental health of workers (p-value) =0.001<=0.05, correlation coefficient=0.443 anda weak relationship between attitudes about Covid -19 and mental health (p-value) = 0.018 < = 0.05 correlation coefficient value=0.294). There is a relationship between knowledge and attitudes about Covid-19 with the mental health of nurses. It is suggested, particularly to the local Hospital of South east Sulawesi, tomake a policy to improve the mental health status of nurses.